Electrified voices : how the telephone, phonograph, and radio shaped modern Japan, 1868-1945 - Yasar, Kerim (Studies of the Weatherhead East Asian Institute, Columbia University., 2018)
Kerim Yasar traces the origins of the modern soundscape, showing how the revolutionary nature of sound technology and the rise of a new auditory culture played an essential role in the formation of Japanese modernity. Electrified Voices is a far-reaching cultural history of the telegraph, telephone, phonograph, radio, and early sound film in Japan.